2020
DOI: 10.1039/d0dt01831g
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field and dilution effects on the slow relaxation of {Er3} triangle-based arsenotungstate single-molecule magnets

Abstract: A triangular {Er3} cluster containing polyoxometalate (POM), [Er3(μ3-OH)(H2O)8(AsW9O33)(AsW10O35(DL-mal))]222− (1) (mal = malate), has been obtained via one-pot reactions. Structural analyses demonstrate that three Er3+ ions bridged one μ3-OH to generate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…It worth noting that the χ M T values of two complexes fall steadily with cooling before dropping rapidly to just 9.33 cm 3 K mol –1 for complex 1 and 4.43 cm 3 K mol –1 for complex 2 at 2 K, respectively. The decrease in χ M T value can be attributed to the progressive depopulation of the Dy III /Er III ion excited Stark sublevels and/or the possible intermolecular antiferromagnetic interactions between neighboring Dy III /Er III ions at low temperature. , …”
Section: Resultsmentioning
confidence: 99%
“…It worth noting that the χ M T values of two complexes fall steadily with cooling before dropping rapidly to just 9.33 cm 3 K mol –1 for complex 1 and 4.43 cm 3 K mol –1 for complex 2 at 2 K, respectively. The decrease in χ M T value can be attributed to the progressive depopulation of the Dy III /Er III ion excited Stark sublevels and/or the possible intermolecular antiferromagnetic interactions between neighboring Dy III /Er III ions at low temperature. , …”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, massive research efforts have been focusing on Tb and Eu mixed-Ln compounds which stem from their visible linelike emission, long lifetime, and efficient energy transfer (ET). For example, some Eu/Tb-doped compounds are capable of achieving tunable emitting colors from green to red upon UV irradiation driven by the Tb 3+ → Eu 3+ ET process, thereby making them promising light-emitting materials . The exploration of Ln cations reacting with lacunary polyoxometalate (POM) units has been a widely used strategy to implement Ln-POM compounds, since Ln 3+ ions can easily react with different POM units by means of the stronger affinity for the surface oxygen atoms of POM. As an important branch of POMs, the arsenotungstates have been attracting considerable attention due to their fascinating structural diversity as well as their wide application prospects. Meanwhile, the introduction of Ln 3+ ions into lacunary arsenotungstates has been proven to be an effective strategy to build up Ln-implanted arsenotungstates with novel luminescence and magnetic properties. …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most of these studies focus solely on the photoluminescence (PL) properties of Ln-POM derivatives, [20][21][22][23][24][25][26][27][28] although there are a few examples demonstrating SMM behaviors. [29][30][31][32][33][34] It is becoming widely accepted that the coordination environment of the Ln center has a great influence on the dynamic relaxation processes of Ln-SMMs. [35][36][37][38][39][40][41] Therefore, several ligands have been reported to coordinate with Ln cations and their effects on magnetic behaviors have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…31 Very recently, our group obtained a novel μ 3 -O-capped {Er 3 } cluster containing the POM K 20 O, which displays field-induced SMM behavior with two magnetic relaxation processes. 34 In particular, Nd-based SMMs are relatively less studied, [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] with only two successful examples of Nd-POM SMMs having being reported to date. 62,63 In detail, Baldoví et al reported the first example of the structure of the Nd-POM singleion magnet [Nd(W 5 O 18 ) 2 ] 9− with an effective barrier of 51.4 cm −1 under an applied field in 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation